Influence of climatic factors and nest tree characteristics on the Nest Structures of the baya weaver (Ploceus philippinus) in Peninsular Malaysia - Thiruvenggadam, Thiruvinothini; Mohd. Top, Marina; Nulit, Rosimah; Puan, Chong Leong (Multidisciplinary Digital Publishing Institute, 2022)
The baya weaver (Ploceus philippinus: Ploceidae), found across South and Southeast Asia, is known for its oblique-shaped overhanging nests. During the breeding season, females select from partially built (‘helmet’-stage) nests constructed by the males, after which nests are completed and used by the birds. Reproductive success is linked to an optimal microclimate within these nest structures. We recorded nest tree and nest structure characteristics of 66 fully completed nests for 22 colonies located in two climatically dissimilar sites in Peninsular Malaysia and examined how these factors affected the microclimate within six nests that were randomly selected at each location. Total vertical length of the nests, the height of nests from the ground, and the diameter at breast height of the nest trees recorded for the Selangor and Perlis colonies (in the southwest and north, respectively), were significantly different. The climatic variables inside and outside the nests correlated significantly in both sites. Our findings indicate that nest structures differed in Selangor and Perlis and were linked to nest microclimate, possibly being influenced by the surrounding temperature.